RETRACTED: 1, 25-D3 Protects From Cerebral Ischemia by Maintaining BBB Permeability via PPAR-γ Activation - Guo, Ting; Wang, Yanqiang; Guo, Yuanfang; Wu, Shuguang; Chen, Weiwei; Liu, Na; Wang, Yu; Geng, Deqin (Frontiers in Cellular Neuroscience, 2018)
The blood-brain barrier (BBB) is a physical and biochemical barrier that maintains cerebral homeostasis. BBB dysfunction in ischemic stroke results in brain injury and subsequent neurological impairment. The aim of this study was to determine the possible protective effects of 1, 25-dihydroxyvitamin D3 [1, 25(OH)2D3, 1, 25-D3, vit D] on BBB dysfunction in the early stages of acute ischemic brain injury. We analyzed the effects of 1, 25-D3 on BBB integrity in terms of histopathological changes, the neurological deficit, infarct size and the expression of brain derived neurotrophic factor (BDNF) in a rat model of middle cerebral artery occlusion/reperfusion (MCAO/R). BBB permeability and the expression of permeability-related proteins in the brain were also evaluated by Evans blue staining and Western blotting respectively. To determine the possible mechanism underlying the role of 1, 25-D3 in BBB maintenance after MCAO/R, the rats were treated with the specific peroxisome proliferator-activated receptor gamma (PPARγ) inhibitor GW9662. Supplementation with 1, 25-D3 markedly improved the neurological scores of the rats, decreased the infarct volume, prevented neuronal deformation, and upregulated the expression of the tight junction and BDNF proteins in their brains. Furthermore, it activated PPARγ but downregulated neuro-inflammatory cytokines like nuclear factor kappa-B (NF-κB) and tumor necrosis factor-α (TNF-α) after MCAO/R. Taken together, 1, 25-D3 protects against cerebral ischemia by maintaining BBB permeability, upregulating the level of BDNF and inhibiting PPARγ-mediated neuro-inflammation.